Bis(acetylacetonato-kappa 2 O,O')[copper(II)nickel(II)(0.31/0.69)]: a mixed-metal complex - Shahid, M.; Hamid, M.; Mazhar, M.; Malik, M.A.; Raftery, J. (International Union of Crystallography, 2010)
The title complex, [Cu(0.31)Ni(0.69)(C(5)H(7)O(2))(2)], was isolated from the reaction of bis(N,N-dimethyaminoethanol)copper(II) with bis(acetylacetonato)nickel(II), which yielded crystals with mixed sites at the central metal position; the refined copper-nickel occupancy ratio is 0.31 (4):0.69 (4). Two acetylacetonate ligands, related by a centre of symmetry, are coordinated to the central metal atom in a square-planar configuration while the methyne C atoms of the acetylacetonate ligands, ca 3.02 A away, are orthogonal to this plane at the metal site.